A Sociolinguistic Analysis of Ondo Dialectal Influence on English Pronunciation of Selected Indigenes in Communicative Situations - Adesuyi, Adesuyi; Adesanmi, T. O.; Adeuga, Folake (International Journal of Independent Research Studies, 2025)
This article focuses on the phonological problems of Yoruba speakers of English as a second language. It results from the concern that there have been hindrances to the free flow of communication between the Ondo speakers of English and people from the other parts of the country bringing about communication controversy among them. The data was gathered with the usage of questionnaire and interview which is recorded on phone and analysed qualitatively based on Chomsky and Halle’s (1968) Generative theory. It was discovered that the Ondo native speakers of English use sounds, stress, syllable, tone and rhythm of their mother tongue in place of those of the target language. Also, they suffer from direct transfer of some items in their mother tongue into what they say in English. In addition, people easily know where they come from through the intonation they use whenever they speak and it could be embarrassing. In conclusion, the study proffered solutions that would enhance better communication and easy learning of the English language by them, looking at the systems of the Ondo dialect in terms of increasing knowledge of the phonological problems which will influence further research in its relationship with English language.